Synergies and tradeoffs in software reuse – a systematic mapping study. (1st August 2016) - Bombonatti, Denise; Goulão, Miguel; Moreira, Ana
Summary: Software reuse is a broadly accepted practice to improve software development quality and productivity. Although an object of study in software engineering since the late sixties, achieving effective reuse remains challenging for many software development organizations. This paper reports a systematic mapping study on how reusability relates to other non‐functional requirements and how different contextual factors influence the success of a reuse initiative. The conclusion is that the relationships are discussed rather informally, and that human, organizational, and technological domain factors are extremely relevant to a particular reuse context. This mapping study highlights the need for further research to better understand how exactly the different non‐functional requirements and context factors affect reusability. Copyright © 2016 John Wiley & Sons, Ltd.